Cobalt-free positive electrode material, preparation method thereof, positive plate and battery
By introducing Mg and Al doping into the cobalt-free high-nickel positive electrode material and introducing B elements on the surface to form a cladding layer, the problem of insufficient structural stability of the material is solved, and higher electrochemical performance and longer service life are achieved.
Patent Information
- Application Number
- CN202411463452.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The structural stability of existing cobalt-free high-nickel cathode materials is insufficient, which makes it difficult for lithium batteries to fully utilize their performance during use, restricting their application in the market.
A cobalt-free cathode material with a core-shell structure has a core chemical formula of LiaNixMgyAlzO2. Mg and Al doping are introduced by in-situ wet chemical coating method, and B elements are introduced on the surface of the material to form a cladding layer to improve the overall and surface stability of the material.
It significantly improves the structural stability of cobalt-free cathode materials, inhibits phase changes and electrolyte corrosion, extends the service life of the battery, and improves electrochemical performance.
Smart Images

Figure CN119542375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a cobalt-free positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. Background Art
[0002] Lithium-ion batteries (LIBs) have superior high energy density and high discharge specific capacity, and have been widely welcomed in portable electronic products, electric vehicles and other fields. In addition, lithium batteries are environmentally friendly, can be cycled for a long time, and provide a reliable and low-cost solution for renewable energy storage. In lithium-ion batteries, the positive electrode material plays a vital role in the key components of lithium batteries.
[0003] Among the positive electrode materials of lithium batteries, ternary positive electrode materials include lithium nickel cobalt manganese oxide LiNi x Co y Mn z O 2 and lithium nickel cobalt aluminum oxide LiNi x Co y Al z O 2 (x+y+z=1), which has attracted much attention due to its high voltage platform and high gram capacity. In recent years, the demand for low-cost and high-energy cathode materials has been increasing, which has promoted the development of cobalt-free (Co-free) and nickel-rich (Ni-rich) cathode materials. However, increasing the nickel content brings certain challenges. For example, the cathode is more susceptible to irreversible phase transitions during the delithiation process. Therefore, the structural integrity of the cathode material may degrade over time, negatively affecting the battery life. In particular, the high delithiation state triggers severe irreversible phase transitions, leading to the formation of a rock salt phase of nickel oxide (NiO) and rapid failure of the cathode material. In addition, during the synthesis and cycling process, nickel ions and lithium ions (Ni 2+ and Li + ) in size promotes the Ni 2+ Migration from the transition metal layer to the Li layer. This migration leads to substantial cation disorder, hindering the Li + The transport of ions and the compromise of the structural integrity of the material. In addition, the cyclic stress generated during battery operation can cause cracks, allow electrolyte penetration and promote corrosion. These problems become particularly prominent when the battery is operated at a high cut-off voltage above 4.5V.
[0004] Element doping is widely regarded as an effective method to improve the stability of positive electrode materials. In nickel-rich positive electrode materials, manganese and cobalt are generally considered to be essential cations. However, the scarcity and toxicity of cobalt (Co), as well as the increased dissolution tendency of manganese (Mn), have prompted the development of positive electrode materials that do not contain Mn and Co to alleviate these shortcomings. At present, a variety of metal elements have been used to replace Mn and Co in high-nickel positive electrode materials. However, the structural stability of high-nickel positive electrode materials or cobalt-free high-nickel positive electrode materials obtained by existing methods needs to be further improved, which makes it difficult for lithium batteries to fully exert their performance during use, restricting their application in the market.
[0005] Therefore, the development or further improvement of cobalt-free positive electrode materials becomes more important. Summary of the invention
[0006] In view of this, the present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a cobalt-free positive electrode material and a preparation method thereof, a positive electrode sheet and a battery, which can improve the structural stability of the positive electrode material and help improve the electrochemical performance of the battery using the positive electrode material.
[0007] In order to solve the above technical problems, this application is implemented as follows:
[0008] According to one aspect of the present application, an embodiment of the present application provides a cobalt-free positive electrode material, the chemical formula of the cobalt-free positive electrode material is Li a Ni x Mg y Al z O 2 nB;
[0009] Among them, 0.9≤a≤1.1, 0<n≤0.1, 0<x<1, 0<y<1, 0<z<1, 1≤x+y+z≤1.2;
[0010] The cobalt-free positive electrode material has a core-shell structure, and the chemical formula of the core of the cobalt-free positive electrode material is Li a Ni x Mg y Al z O 2 , wherein Mg is an element for doping and replacing Li at the alkali metal site, and Al is an element for doping and replacing Ni at the transition metal site;
[0011] A coating layer is formed on the surface of the core, and the coating layer contains element B.
[0012] In addition, the cobalt-free positive electrode material according to the present application may also have the following additional technical features:
[0013] In some embodiments, x, y, and z satisfy:
[0014] 0.6≤x≤0.95, 0<y≤0.2, 0<z≤0.2.
[0015] In some embodiments, a satisfies: 0.95≤a≤1.05.
[0016] In some embodiments, x, y and z satisfy: 1.05≤x+y+z≤1.1.
[0017] In some embodiments, the particle size Dv50 of the inner core is 1 μm to 8 μm.
[0018] In some embodiments, the coating layer has a thickness of 2 nm to 10 nm.
[0019] In some embodiments, the element B exists in at least one of the following forms:
[0020] (1) forming a coating layer on the surface of the core;
[0021] (2) replace nickel ions in the lithium nickelate lattice;
[0022] (3) Replace lithium ions in the lithium nickel oxide lattice.
[0023] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a cobalt-free positive electrode material, the method comprising:
[0024] Mixing the nickel-containing compound, the co-solvent and water to obtain a mixed solution;
[0025] Adding a magnesium-containing compound and an aluminum-containing compound to the mixed solution, and obtaining a precursor after mixing, separating and drying;
[0026] The precursor is mixed with a boron-containing compound and a lithium-containing compound, and sintered to obtain the cobalt-free positive electrode material.
[0027] In some embodiments, the nickel-containing compound includes at least one of nickel hydroxide, nickel chloride or nickel nitrite.
[0028] In some embodiments, the co-solvent includes polyvinyl pyrrolidone.
[0029] In some embodiments, the magnesium-containing compound includes at least one of magnesium chloride, magnesium hydroxide, magnesium nitrate or magnesium sulfite.
[0030] In some embodiments, the aluminum-containing compound includes at least one of sodium aluminate, aluminum hydroxide, aluminum carbonate or aluminum sulfite.
[0031] In some embodiments, the boron-containing compound includes at least one of boric acid, boron chloride or boron oxide.
[0032] In some embodiments, the lithium-containing compound includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate or lithium chloride.
[0033] In some embodiments, the mass ratio of the nickel-containing compound to the co-solvent is (10-25):1.
[0034] In some embodiments, the nickel-containing compound, the co-solvent and water are mixed and stirred at a temperature of 60° C. to 80° C. for 1 h to 4 h to obtain a mixed solution.
[0035] In some embodiments, the particle size Dv50 of the precursor is 3 μm to 5 μm.
[0036] In some embodiments, the tap density of the precursor is 1.5 to 1.9 g / cm 3 .
[0037] In some embodiments, in the step of obtaining the precursor, the magnesium-containing compound is first added to the mixed solution and stirred for 1 h to 5 h, and then the aluminum-containing compound is added to the mixed solution and stirred for 2 h to 5 h. After mixing evenly, separation, washing and drying are performed.
[0038] In some embodiments, in the step of obtaining the cobalt-free positive electrode material, the precursor, the boron-containing compound and the lithium-containing compound are mixed in a molar ratio of Ni:Mg:Al:B:Li=x:y:z:n:a, and then preheated at 300°C to 500°C for 4h to 8h, and then sintered at 600°C to 820°C for 10h to 16h to obtain the cobalt-free positive electrode material.
[0039] According to another aspect of the present application, an embodiment of the present application provides a positive electrode sheet, which includes the aforementioned cobalt-free positive electrode material, or the cobalt-free positive electrode material prepared according to the aforementioned method.
[0040] According to another aspect of the present application, an embodiment of the present application provides a battery, which includes the aforementioned cobalt-free positive electrode material, or the cobalt-free positive electrode material prepared according to the aforementioned method, or the aforementioned positive electrode sheet.
[0041] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0042] In the embodiment of the present application, the cobalt-free positive electrode material provided is a core-shell structure, and the chemical formula of the core is Li a Nix Mg y Al z O 2 , wherein magnesium (Mg) is an element doped to replace lithium (Li) in the alkali metal position, and aluminum (Al) is an element doped to replace nickel (Ni) in the transition metal position; the coating layer contains the element boron (B). Thus, by doping Mg and Al into lithium nickel oxide (LiNiO 2 ) material, and at the same time, the B element is introduced in situ to dope the surface of the material. Mg and Al are mainly located inside the particles, and B is mainly located on the surface, thereby improving the overall and surface stability of the cobalt-free positive electrode material. Compared with the common materials on the market, the structural stability of the cobalt-free positive electrode material of the present application has been significantly increased. The excellent structural stability of the cobalt-free positive electrode material can effectively inhibit phase changes, prevent secondary particle cracking, and reduce electrolyte corrosion, thereby further expanding the scope of cobalt-free positive electrode materials.
[0043] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Shown are charge and discharge curves of some embodiments and comparative examples of the present invention.
[0045] Figure 2 Shown are schematic diagrams of long cycle curves of some embodiments and comparative examples of the present invention.
[0046] Figure 3 Shown is a schematic diagram of density functional theory (DFT) calculation provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0047] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0048] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0049] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0050] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0051] Cobalt-free positive electrode materials can reduce the cost of positive electrode materials by not using cobalt elements. However, due to the lack of cobalt elements, cobalt-free positive electrode materials will also lead to poor stability of the layered structure of the positive electrode materials, affecting the material's cycle performance and rate performance and other properties. Therefore, it is also necessary to modify the cobalt-free positive electrode materials. In the existing modification treatments, element doping is widely considered to be one of the effective methods to improve the stability of positive electrode materials. In cobalt-free positive electrode materials or cobalt-free high-nickel positive electrode materials, a variety of metal elements have been used to replace Mn and Co. For example, magnesium and aluminum are low-cost and easily available elements, and are often used in the modification of nickel-rich layered oxide positive electrode materials. However, the existing cobalt-free positive electrode materials still have certain shortcomings. For example, the structural stability of the existing cobalt-free positive electrode materials needs to be further improved.
[0052] In view of this, the present application provides a cobalt-free positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. The present invention mainly adopts an in-situ wet chemical coating method (through AlO 2- and Mg 2+ Mg and Al are incorporated into lithium nickel oxide (LiNiO 2 ) positive electrode material (denoted as NMA), and the boron (B) element is introduced in situ to dope the surface of the material. Mg and Al are mainly located inside the particles, and B is mainly located on the surface, thereby improving the overall and surface stability of the cobalt-free positive electrode material, that is, improving the structural stability of the cobalt-free positive electrode material. Compared with the common materials on the market, the cobalt-free positive electrode material provided by the present invention has significantly increased structural stability. The cobalt-free positive electrode material not only has excellent structural stability, but also can effectively inhibit phase changes, prevent secondary particle cracking, and reduce electrolyte corrosion, thereby further expanding the scope of cobalt-free positive electrode materials. The present application is described in detail below.
[0053] In some embodiments, the present application provides a cobalt-free cathode material, the chemical formula of which is Li a Ni x Mg y Al z O 2 nB;
[0054] Among them, 0.9≤a≤1.1, 0<n≤0.1, 0<x<1, 0<y<1, 0<z<1, 1≤x+y+z≤1.2.
[0055] In the present application, the cobalt-free cathode material has a core-shell structure, and the chemical formula of the core of the cobalt-free cathode material is Li a Ni x Mg y Al z O 2 , wherein magnesium (Mg) is an element that is doped to replace lithium (Li) at the alkali metal site, and aluminum (Al) is an element that is doped to replace nickel (Ni) at the transition metal site;
[0056] A coating layer is formed on the surface of the inner core, and the coating layer contains elemental boron (B).
[0057] In the present invention, the provided cobalt-free positive electrode material has a coating layer, and the cobalt-free positive electrode material with the coating layer has a core-shell structure, the core (inner core) is lithium nickelate doped with lithium and nickel elements, and the shell is the coating layer.
[0058] It should be noted that in the present application, the term "coating" is not limited to direct coating, but also includes indirect coating. For example, the coating layer coats the core, and there may be no other structure between the coating layer and the outer surface of the core, or there may be one or more layers of other structures between the coating layer and the outer surface of the core. Preferably, there is no other structure between the coating layer and the outer surface of the core.
[0059] The above-mentioned coating layer can be formed on at least part of the surface of the core, which can play a role in protecting the core. For example, the presence of the coating layer can avoid the contact between the matrix core and the electrolyte, alleviate the side reactions between the matrix core material and the electrolyte, improve the surface stability of the cobalt-free positive electrode material, and thus help improve the overall structural stability and cycle stability of the cobalt-free positive electrode material. The coating layer is formed or coated on at least part of the surface of the core, which means that the coating layer can completely encapsulate the core in the coating layer, or the coating layer can only coat a part of the outer surface of the core; that is, the coating layer can completely coat the core, or it can coat part of the surface of the core.
[0060] According to an embodiment of the present invention, the chemical formula Li a Ni x Mg y Alz O 2 In nB, a is 0.9 to 1.1, preferably, a is 0.95 to 1.1, and more preferably, a is 0.95 to 1.05. For example, a may be any one of 0.9, 0.92, 0.95, 0.97, 0.98, 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, and 1.1, or a range between any two of them.
[0061] x is 0 to 1 (excluding 0 and 1), preferably 0.5 to 0.95, and more preferably 0.6 to 0.95. For example, x can be any one of 0.1, 0.2, 0.4, 0.5, 0.6, 0.7, 0.8, 0.85, 0.89, 0.9, 0.92, and 0.95, or a range between any two of them.
[0062] y is 0 to 1 (excluding 0 and 1), preferably 0.01 to 0.5, and more preferably 0.01 to 0.2. For example, y can be any point value among 0.01, 0.02, 0.03, 0.05, 0.08, 0.1, 0.15, 0.18, 0.2, 0.3, 0.4, 0.5, 0.6, etc., or a range value between any two of them.
[0063] z is 0 to 1 (excluding 0 and 1), preferably 0.01 to 0.5, and more preferably 0.01 to 0.2. For example, z can be any point value among 0.01, 0.02, 0.05, 0.08, 0.1, 0.11, 0.15, 0.18, 0.2, 0.3, 0.4, 0.5, 0.6, etc., or a range value between any two of them.
[0064] n is 0 to 0.1 (excluding 0), preferably 0 to 0.08. For example, n can be any one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.1, or a range between any two of them.
[0065] In the present invention, the cobalt-free positive electrode material provided is a surface-modified doped cobalt-free positive electrode material, that is, the cobalt-free positive electrode material is an element B-modified lithium nickelate positive electrode material doped with metal elements Mg and Al.
[0066] The cobalt-free positive electrode material of the present invention can greatly improve the comprehensive performance of the cobalt-free positive electrode material by regulating the type of doping elements, the doping amount of doping elements, and the position of doping elements, and giving full play to the advantages of different doping elements. The metal element Mg can be doped at the lithium position in lithium nickelate, and the metal element Al can be doped at the nickel position in lithium nickelate. Mg and Al can play the role of double-column support, which can be used to improve the structural stability of the cobalt-free positive electrode material and increase the capacity of the material; element B can be used to improve the overall and surface stability of the cobalt-free positive electrode material through surface modification, thereby improving the cycle stability and first coulomb efficiency of the cobalt-free positive electrode material.
[0067] Specifically, the chemical formula Li a Ni x Mg y Al z O 2 Compared with LiNiO 2 Substitution of small metal ions Mg 2+ Can easily enter the Li site, + Partial substitution; while the larger ion Al 3+ Usually doped into transition metal layered structures, this doping strategy enhances the structural stability of cathode materials, prevents collapse along the c direction under high pressure, and suppresses phase transitions. In addition, B helps to form a protective surface NiO layer of about 200 μm, reducing surface activity and minimizing adverse side reactions. In addition, smaller primary particles help to alleviate stress-induced cracks, further enhancing mechanical stability.
[0068] In other words, the Mg in the alkali metal position of Li in the present invention plays the role of a pillar, which can inhibit interlayer slip during charge and discharge and stabilize anionic oxygen. Al in the transition metal position of Ni can increase the average working voltage and is conducive to stimulating anionic redox. 2+ Radius and Li + The valence state of magnesium is stable, and some magnesium will enter the lithium position, which can inhibit the collapse of the nickel oxide layer during the charge and discharge process, which can not only improve the structural stability of the material, but also avoid hindering the insertion and extraction of lithium; in addition, Al 3+There is no electrochemical activity, and the valence state is stable, which can limit the transitional deintercalation of lithium ions, and is also beneficial to stabilize the structural stability of the material and improve the cycle performance of the material. Thus, the present invention further improves the structural stability of the cobalt-free positive electrode material through the combination of Mg and Al, and can also achieve the effect of the high capacity of the cobalt-free positive electrode material, so the cobalt-free positive electrode material provided by the present invention has a higher charge and discharge specific capacity and cycle performance. In addition, the present invention is surface-modified by element B, and can be doped on the outer surface of the kernel to form a coating layer, especially a nano-coating layer, which can reduce the surface activity of the material, inhibit the contact between the high-nickel cobalt-free matrix material and the electrolyte, and slow down the side reactions between the high-nickel cobalt-free matrix material and the electrolyte, which is beneficial to improve the overall and surface stability of the cobalt-free positive electrode material, thereby improving the cycle stability and first coulomb efficiency of the cobalt-free positive electrode material.
[0069] It should be noted that in the cobalt-free positive electrode material of the present invention, the doping substitution position of the doping element can be obtained by density functional theory (DFT) calculation or analysis, which is used to illustrate that Mg is an element that is doped to replace Li at the alkali metal position, and Al is an element that is doped to replace Ni at the transition metal position. Figure 3 As shown, by introducing density functional theory (DFT), the energy of Mg and Al in the Ni layer and Li layer are calculated respectively, so as to accurately determine their (Mg and Al) positions in the material. Among them, Mg requires 0.743 eV to occupy the Li layer and 1.681 eV to occupy the Ni layer, which indicates that Mg has a higher probability of occupying the Li layer. On the other hand, Al is more likely to reside in the Ni layer because the energy required to occupy the Ni site (1.046 eV) is lower than that to occupy the Li site (1.974 eV). In addition, this observation can be explained by the energy of Mg2 and Li (0.72 and 1.681 eV, respectively). ) and Al3 and Ni3 (0.54 and ) can be explained by the similarity of their ionic radii.
[0070] It should also be pointed out that in the cobalt-free positive electrode material of the present application, the coating layer contains element B. In addition, the coating layer may also contain other elements, that is, the coating layer may be a compound containing B. For example, the B-containing compound may also contain O element, or may also contain Li element, etc. The present application does not limit the specific composition of the compound.
[0071] In some embodiments, x, y, and z satisfy: 0.6≤x≤0.95, 0<y≤0.2, and 0<z≤0.2. As an example, x can be any point value of 0.6, 0.65, 0.7, 0.8, 0.85, 0.89, 0.9, and 0.95, or a range value between any two of them. y can be any point value of 0.01, 0.02, 0.03, 0.04, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, and 0.2, or a range value between any two of them. z can be any point value of 0.01, 0.02, 0.03, 0.04, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, and 0.2, or a range value between any two of them.
[0072] In some embodiments, x, y and z satisfy: 1≤x+y+z≤1.2. Preferably, x, y and z satisfy: 1≤x+y+z≤1.1. More preferably, x, y and z satisfy: 1.05≤x+y+z≤1.1.
[0073] In the present invention, the stoichiometric ratio of the core in the cobalt-free positive electrode material is further limited, so that the high discharge specific capacity and cycle stability of the cobalt-free positive electrode material can be better achieved, especially the stoichiometric ratio of nickel is within the range of 0.6≤x≤0.95, which increases the stoichiometric ratio of nickel. By increasing the stoichiometric ratio of nickel, it is beneficial to achieve the high capacity of the positive electrode material and the high energy density of the battery cell. However, if x is too large, it is easy to cause lithium-nickel mixing, which will not only reduce the discharge specific capacity of the material, but also reduce the structural stability of the material; if x is too small, it will lead to a decrease in the discharge specific capacity. The present invention not only helps to improve the capacity of the material, but also improves the cycle stability of the material through the synergistic effect of high nickel and magnesium aluminum.
[0074] Therefore, the provided cobalt-free positive electrode material is a high-nickel cobalt-free and manganese-free positive electrode material, which has good structural stability, realizes the high capacity of the positive electrode material, and also improves the cycle stability of the positive electrode material.
[0075] In some embodiments, the particle size Dv50 of the core is 1 μm to 8 μm. Preferably, the particle size Dv50 of the core is 2 μm to 6 μm. As an example, the particle size Dv50 of the core can be any one of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or a range between any two of them.
[0076] By making the particle size of the core within the above-mentioned appropriate range, the processing performance of the material can be improved, and the use of a core with a smaller particle size is conducive to improving the first coulombic efficiency of the material, or improving the rate performance of the material, so that the comprehensive electrical performance of the cobalt-free positive electrode material can be better.
[0077] In some embodiments, the coating layer has a thickness of 2 nm to 10 nm. Preferably, the coating layer has a thickness of 3 nm to 8 nm. As an example, the coating layer may have a thickness of 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or any range between two of them.
[0078] The present invention reduces the surface activity of the positive electrode material by coating the core of the cobalt-free positive electrode material such as the high-nickel cobalt-free and manganese-free positive electrode material, which can inhibit the side reaction between the electrolyte and the positive electrode material, and is beneficial to prolonging the service life of the positive electrode material and reducing the gas production of the battery. The thickness of the coating layer can be adjusted according to the size of the core. The appropriate thickness of the coating layer can ensure that the cobalt-free positive electrode material has good processing performance, and can avoid the thickness being too thick, the coating material increasing the battery impedance or affecting the cycle performance of the battery, or can also avoid the thickness being too thin to effectively exert the modification effect of the coating layer, that is, to avoid the thickness being too thin to effectively improve the surface stability of the material.
[0079] In some embodiments, element B is present in at least one of the following forms:
[0080] (1) forming a coating layer on the surface of the core;
[0081] (2) replace nickel ions in the lithium nickelate lattice;
[0082] (3) Replace lithium ions in the lithium nickel oxide lattice.
[0083] In the cobalt-free positive electrode material of the present application, element B is mainly located on the surface, forming a modified layer on the surface of the material; in addition, element B can also be doped into the bulk phase of lithium nickelate due to its small ion radius, such as element B can replace nickel ions in the lithium nickelate lattice, or replace lithium ions in the lithium nickelate lattice; in this way, it can not only stabilize the surface stability, but also stabilize the oxygen skeleton, which is beneficial to improve the cycle stability and first charge efficiency of the cobalt-free positive electrode material.
[0084] Therefore, based on the above, the provided cobalt-free cathode material is a cobalt-free cathode material supported by Mg and Al double pillars and doped with B element on the surface, wherein the Mg and Al doping sites are located in the Li layer and the Ni layer, respectively, forming a unique double pillar structure. In the cobalt-free cathode material, the presence of the Mg and Al double pillar structure has an important effect on inhibiting the Li + and Ni 2+ The mixing of Mg and Al plays a crucial role, thereby reducing cation disorder and preventing irreversible phase transition. In addition, the introduction of Mg and Al enhances the kinetics of the cathode material and significantly improves the Li +The diffusion coefficient of Mg and Al is reduced, which reduces the charge transfer impedance. Another significant benefit of Mg and Al doping is the ability to refine the elementary particles of the cathode material, thereby minimizing the occurrence of cracks.
[0085] The present invention enhances mechanical and surface chemical stability by using a unique element mixing method. The elements magnesium and aluminum are mainly located inside the particles, while boron is mainly located on the surface. This unique element configuration significantly improves the overall phase and surface structure stability of the material.
[0086] In some embodiments, the present application provides a method for preparing a cobalt-free positive electrode material, the method comprising:
[0087] Mixing the nickel-containing compound, the co-solvent and water to obtain a mixed solution;
[0088] Adding a magnesium-containing compound and an aluminum-containing compound to the mixed solution, mixing, separating and drying to obtain a precursor;
[0089] The precursor is mixed with a boron-containing compound and a lithium-containing compound, and sintered to obtain a cobalt-free positive electrode material.
[0090] In the present invention, by in-situ wet chemical coating (through AlO 2- and Mg 2+ Mg and Al are incorporated into LiNiO by reaction of 2 In the positive electrode material, the B element is introduced in situ to dope the material surface. Mg and Al are mainly located inside the particles, and B is mainly located on the surface.
[0091] Thus, the provided cobalt-free cathode material is a cobalt-free cathode material supported by Mg and Al double pillars. The B surface doped Mg and Al double pillar LiNiO was successfully synthesized by in situ wet chemical coating method. 2 The method is simple to operate, has a short process, low energy consumption, and is easy to realize industrial production.
[0092] In the preparation method of the present invention, nickel-containing compounds such as Ni(OH) 2 As the substrate, LN material was substituted, Mg replaced Li site, Al was added to the layered structure of NiO, and B element was introduced in situ to dope the material surface to synthesize B surface doped Mg and Al double-pillar LiNiO 2 That is, the cobalt-free positive electrode material of the present invention is mainly relative to LiNiO 2 Substitution of small metal ions Mg 2+ Can easily enter the Li site, + Partial substitution; while the larger ion Al 3+Usually doped into transition metal layered structures, this doping strategy enhances the structural stability of cathode materials, prevents collapse along the c direction under high pressure, and suppresses phase transitions. In addition, B helps to form a protective surface NiO layer of about 200 μm, reducing surface activity and minimizing adverse side reactions. In addition, smaller primary particles help to alleviate stress-induced cracks, further enhancing mechanical stability.
[0093] It should be understood that all the features and advantages described above for the “cobalt-free positive electrode material” are also applicable to the “method for preparing cobalt-free positive electrode material” and will not be described in detail here.
[0094] In some specific embodiments, the method for preparing the cobalt-free positive electrode material specifically comprises the following steps (a) to (c):
[0095] (a) Prepare a mixed solution.
[0096] In step (a), preparing the mixed solution comprises: mixing the nickel-containing compound, a co-solvent and water to obtain a mixed solution (suspension).
[0097] Specifically, step (a) comprises: adding the nickel-containing compound and the co-solvent to water (such as deionized water) in a certain weight ratio in sequence, that is, mixing the nickel-containing compound, the co-solvent and the water, stirring them at a temperature of 60°C to 80°C (such as 60°C, 65°C, 70°C, 75°C, 80°C, etc.) for 1h to 4h (such as 1h, 2h, 2.5h, 3h, 3.5h, 4h, etc.) to fully mix them to obtain a mixed solution.
[0098] In step (a), the addition of a co-solvent can play a role in promoting dissolution and bonding.
[0099] In some embodiments, the nickel-containing compound includes, but is not limited to, nickel hydroxide (Ni(OH) 2 ), nickel chloride (NiCl 2 ) or nickel nitrite (Ni(NO 2 ) 2 ) or a combination of at least two of them.
[0100] Preferably, the nickel-containing compound is selected from (Ni(OH) 2 .
[0101] In some embodiments, the co-solvent includes polyvinyl pyrrolidone (PVP), which can play a role of solubilization and binding.
[0102] In some embodiments, the mass ratio of the nickel-containing compound to the co-solvent is (10-25): 1. Preferably, the mass ratio of the nickel-containing compound to the co-solvent is (18-22): 1. As an example, the mass ratio of the nickel-containing compound to the co-solvent is 10: 1, 12: 1, 15: 1, 18: 1, 20: 1, 22: 1, 25: 1, etc.
[0103] (b) Preparation of precursor.
[0104] In step (b), preparing the precursor comprises: adding a magnesium-containing compound and an aluminum-containing compound to the mixed solution obtained in step (a), and obtaining the precursor after mixing, separating and drying.
[0105] Specifically, step (b) comprises: adding a certain proportion of a magnesium-containing compound to the mixed solution obtained in step (a), stirring for 1 h to 5 h (such as 1 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 5 h, etc.), then slowly adding a certain proportion of an aluminum-containing compound to the mixed solution, continuously heating and stirring for 2 h to 5 h (such as 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 5 h, etc.), mixing evenly, filtering, washing and drying, and crushing to obtain Mg 2+ and Al 3+ Uniformly doped and coated precursor—Ni x Mg y Al z (OH) 2 .
[0106] In some embodiments, magnesium-containing compounds include, but are not limited to, magnesium chloride (MgCl 2 )、Magnesium hydroxide (Mg(OH) 2 ), magnesium nitrate (Mg(NO 3 ) 2 ) or magnesium sulfite (MgSO 3 ) or a combination of at least two of them.
[0107] Preferably, the magnesium-containing compound is selected from MgCl 2 .
[0108] In some embodiments, aluminum-containing compounds include, but are not limited to, sodium aluminate (NaAlO 2 ), aluminum hydroxide (Al(OH) 3 ), aluminum carbonate (Al 2 CO 3 ) or aluminum sulfite (Al 2 SO 3 ) or a combination of at least two of them.
[0109] Preferably, the aluminum-containing compound is selected from NaAlO 2 .
[0110] In the present application, in step (b), preferably a certain molar ratio of NaAlO is slowly added. 2 Solution (solid-liquid ratio 25-38wt%).
[0111] Among them, nickel-containing compounds such as Ni(OH) 2 、Magnesium compounds such as MgCl 2 , aluminum compounds such as NaAlO 2 The amount of Ni(OH) 2 MgCl 2, NaAlO 2 The molar ratio is the ratio of x, y, and z, wherein 0<x<1, 0<y<1, 0<z<1, and x+y+z=1. Preferably, 0.6≤x≤0.95, 0<y≤0.2, and 0<z≤0.2. Of course, in the actual production process, the raw materials can be added in excess as needed.
[0112] Preferably, the precursor obtained in step (b) is Ni x Mg y Al z (OH) 2 It is spherical or quasi-spherical, preferably spherical.
[0113] In some embodiments, the precursor—Ni x Mg y Al z (OH) 2 The particle size Dv50 of the precursor is 3 μm to 5 μm. Preferably, the particle size Dv50 of the precursor is 3.9±0.2 μm. As an example, the particle size of the precursor can be any one of 3 μm, 3.5 μm, 3.7 μm, 3.9 μm, 4 μm, 4.1 μm, 4.5 μm, 5 μm, or a range between any two of them.
[0114] In some embodiments, the precursor—Ni x Mg y Al z (OH) 2 The tap density is 1.5~1.9g / cm 3 Preferably, the tap density of the precursor is 1.65±0.15 g / cm 3 As an example, the tap density of the precursor may be 1.5 g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm3 Any point value in or any range between two values.
[0115] (c) Mixed lithium sintering.
[0116] In step (c), the lithium-mixed sintering comprises: mixing the precursor obtained in step (b) with a boron-containing compound and a lithium-containing compound, and sintering to obtain a cobalt-free positive electrode material.
[0117] Specifically, step (c) includes: mixing the precursor, the boron-containing compound and the lithium-containing compound according to the molar ratio of Ni:Mg:Al:B:Li=x:y:z:n:a, and then preheating at a temperature of 300°C to 500°C (such as 300°C, 350°C, 380°C, 400°C, 420°C, 450°C, 500°C, etc.) for 4h to 8h (such as 4h, 5h, 6h, 7h, 8h, etc.), and then sintering at a temperature of 600°C to 820°C (such as 600°C, 650°C, 700°C, 740°C, 750°C, 800°C, 820°C, etc.), preferably at 650°C to 740°C for 10h to 16h (such as 10h, 11h, 12h, 13h, 14h, 16h, etc.), preferably 10h to 12h, to obtain a cobalt-free positive electrode material.
[0118] In some embodiments, boron-containing compounds include, but are not limited to, boric acid (H 3 BO 3 ), any one of boron chloride or boron oxide, or a combination of at least two thereof.
[0119] Preferably, the boron-containing compound is selected from H 3 BO 3 powder.
[0120] In some embodiments, the lithium-containing compound includes, but is not limited to, at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, or lithium chloride.
[0121] Preferably, the lithium-containing compound is selected from lithium hydroxide (LiOH·H 2 O).
[0122] The method for preparing the cobalt-free positive electrode material provided in the embodiment of the present invention has a simple process, strong operability, and is suitable for large-scale production.
[0123] In some embodiments, the embodiments of the present application provide a positive electrode sheet, which includes a current collector and a positive electrode active material layer arranged on the surface of the current collector; the positive electrode active material layer includes the aforementioned cobalt-free positive electrode material or the cobalt-free positive electrode material prepared by the aforementioned method.
[0124] The positive electrode sheet includes the above-mentioned cobalt-free positive electrode material provided in the embodiment of the present application, and therefore, the positive electrode sheet also has the characteristic of excellent electrochemical performance.
[0125] The present application has no particular restrictions on the material of the current collector in the positive electrode sheet, as long as the purpose of the present application can be achieved, and it can be selected according to actual needs. For example, in some embodiments, the positive electrode current collector may include aluminum foil, aluminum alloy foil, etc. Of course, in other embodiments, a composite current collector (such as an aluminum-carbon composite current collector) may also be used.
[0126] In some embodiments, the positive electrode active material layer further includes a conductive agent and a binder.
[0127] The present application embodiment has no particular restrictions on the types of conductive agents and binders in the positive electrode active material layer, as long as the purpose of the present application can be achieved. For example, in some embodiments, the binder may include but is not limited to polyacrylate, polyimide, polyvinyl alcohol, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene-butadiene rubber), polytetrafluoroethylene, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose or sodium hydroxymethyl cellulose. One or more. The conductive agent may include but is not limited to at least one of conductive carbon black (such as acetylene black, Ketjen black), carbon nanotubes (CNTs), carbon fibers, graphene, etc. The above-mentioned carbon nanotubes may be single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0128] Optionally, in the positive electrode active material layer, the mass ratio of the cobalt-free positive electrode material, the conductive agent and the binder is (80-98): (1-10): (1-10).
[0129] The present application has no particular restrictions on the preparation method of the positive electrode sheet, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet includes but is not limited to the following steps: dispersing the cobalt-free positive electrode material, the conductive agent, and the binder in N-methylpyrrolidone (NMP) solvent to form a uniform positive electrode slurry, coating the positive electrode slurry on the positive electrode collector, and drying, cold pressing, slitting, etc. to obtain the positive electrode sheet.
[0130] In some embodiments, the embodiments of the present application provide a battery, which includes the aforementioned cobalt-free positive electrode material, or the cobalt-free positive electrode material prepared according to the aforementioned method, or the aforementioned positive electrode sheet.
[0131] The battery includes the above-mentioned cobalt-free positive electrode material provided in the embodiments of the present application. Therefore, the battery, such as a lithium-ion secondary battery, also has the characteristics of excellent electrochemical performance, such as the battery has the characteristics of long cycle life, high discharge specific capacity and good first coulombic efficiency.
[0132] The electrochemical cell may be a secondary battery having high cycle performance and high capacity. Specifically, the secondary battery may be a lithium secondary battery. The battery structure of the present application includes but is not limited to a soft-pack lithium-ion battery, a square hard-shell battery or a cylindrical hard-shell battery, etc.
[0133] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0134] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0135] Example 1
[0136] The preparation of the cobalt-free positive electrode material comprises the following steps:
[0137] (a) 18 g of Ni(OH) 2 and 0.85 g of PVP were mixed in 100 mL of deionized water, and stirred at 70° C. for 1 h to fully mix to obtain a mixed solution.
[0138] (b) Add 0.3 g of MgCl to the mixed solution obtained in step (a). 2 The mixture was stirred for 1 h; then, 30 mL of NaAlO was slowly added to the mixture. 2 The solution (solid-liquid ratio is 0.3wt%) was heated and stirred for 2h. After mixing evenly, it was filtered, washed and dried, and pulverized to obtain Mg 2+ and Al 3+ Uniformly doped and coated precursor—Ni x Mg y Al z (OH) 2 , that is, to obtain Mg(OH) 2 and Al(OH) 3 Uniformly doped and coated Ni(OH) 2 Precursor.
[0139] (c) The above precursors were mixed with H at a molar ratio of B: (Ni+Al): (Mg+Li) = 0.01:1:1.05. 3 BO 3 Powder and LiOH·H 2O was fully mixed to obtain a mixture, and then the mixture was preheated at 480°C for 5 h, and then calcined at 720°C for 12 h in a flowing oxygen atmosphere to obtain a cobalt-free positive electrode material (Li 0.95 Ni 0.89 Mg 0.05 Al 0.11 O 2 ·0.01B).
[0140] Example 2
[0141] Embodiment 2 is substantially the same as Embodiment 1, except that:
[0142] In step (b), add 0.45 g of MgCl 2 The mixture was stirred for 1 h; then, 50 mL of NaAlO was slowly added to the mixture. 2 Solution (solid-liquid ratio is 0.3wt%).
[0143] The chemical formula of the obtained cobalt-free cathode material is Li 0.92 Ni 0.85 Mg 0.08 Al 0.15 O 2 0.01B.
[0144] The rest are the same as in Example 1.
[0145] Example 3
[0146] Embodiment 3 is substantially the same as Embodiment 1, except that:
[0147] In step (b), add 0.2 g of MgCl 2 The mixture was stirred for 1 h; then, 10 mL of NaAlO 2 Solution (solid-liquid ratio is 0.3wt%).
[0148] The chemical formula of the obtained cobalt-free cathode material is Li 0.97 Ni 0.92 Mg 0.03 Al 0.08 O 2 0.01B.
[0149] The rest are the same as in Example 1.
[0150] Example 4
[0151] Embodiment 4 is substantially the same as Embodiment 1, except that:
[0152] In step (c), the mixture was preheated at 430°C for 3 h and then calcined at 600°C for 12 h in a flowing oxygen atmosphere.
[0153] The rest are the same as in Example 1.
[0154] Example 5
[0155] Example 5 is substantially the same as Example 1, except that:
[0156] In step (c), the mixture was preheated at 550°C for 3 h and then calcined at 800°C for 10 h in a flowing oxygen atmosphere.
[0157] The rest are the same as in Example 1.
[0158] Example 6
[0159] Embodiment 6 is substantially the same as Embodiment 1, except that:
[0160] In step (c), the above precursors are mixed with H at a molar ratio of B: (Ni+Al): (Mg+Li) of 0.02:1:1.05. 3 BO 3 Powder and LiOH·H 2 O and mix thoroughly to obtain a mixture.
[0161] The chemical formula of the obtained cobalt-free cathode material is Li 0.95 Ni 0.89 Mg 0.05 Al 0.11 O 2 0.02B.
[0162] The rest are the same as in Example 1.
[0163] Example 7
[0164] Example 7 is substantially the same as Example 1, except that:
[0165] In step (c), the above precursors are mixed with H at a molar ratio of B: (Ni+Al): (Mg+Li) of 0.03:1:1.05. 3 BO 3 Powder and LiOH·H 2 O and mix thoroughly to obtain a mixture.
[0166] The chemical formula of the obtained cobalt-free cathode material is Li 0.95 Ni 0.89 Mg 0.05 Al 0.11 O 2 0.03B.
[0167] The rest are the same as in Example 1.
[0168] Comparative Example 1
[0169] The preparation of the cobalt-free positive electrode material comprises the following steps:
[0170] (a) Ni(OH) 2 and LiOH·H 2 O (molar ratio of 1:1.05) were fully ground and uniformly mixed to obtain a mixture.
[0171] (b) The mixture was preheated at 480 °C for 5 h and then calcined at 720 °C for 12 h in a flowing oxygen atmosphere to obtain pristine LiNiO 2 Positive electrode material.
[0172] The positive electrode material prepared in Comparative Example 1 is conventional lithium nickel oxide (LiNiO 2 ) positive electrode material.
[0173] Comparative Example 2
[0174] The preparation of the cobalt-free positive electrode material comprises the following steps:
[0175] (a) 18 g of Ni(OH) 2 and 0.85 g of PVP were mixed in 100 mL of deionized water, and stirred at 70° C. for 1 h to fully mix to obtain a mixed solution.
[0176] (b) Add 0.3 g of MgCl to the mixed solution obtained in step (a). 2 The mixture was stirred for 1 h; then, 30 mL of NaAlO was slowly added to the mixture. 2 The solution (solid-liquid ratio is 0.3wt%) was heated and stirred for 2h. After mixing evenly, it was filtered, washed and dried, and pulverized to obtain Mg 2+ and Al 3+ Uniformly doped and coated precursor—Ni x Mg y Al z (OH) 2 , that is, to obtain Mg(OH) 2 and Al(OH) 3 Uniformly doped and coated Ni(OH) 2 Precursor.
[0177] (c) The above precursors were mixed with LiOH·H at a molar ratio of (Ni+Al):(Mg+Li)=1:1.05. 2O was fully mixed to obtain a mixture, and then the mixture was preheated at 480°C for 5 h, and then calcined at 720°C for 12 h in a flowing oxygen atmosphere to obtain a cobalt-free positive electrode material (Li 0.95 Ni 0.89 Mg 0.05 Al 0.11 O 2 ).
[0178] The cobalt-free positive electrode material prepared in Comparative Example 2 does not contain element B.
[0179] Performance Testing
[0180] The cobalt-free positive electrode materials prepared in the above embodiments and comparative examples were respectively prepared into batteries, and the performance tests of the batteries were carried out, specifically including:
[0181] 1. Preparation of batteries
[0182] (1) Preparation of positive electrode sheet: The above-mentioned cobalt-free positive electrode material, binder polyvinylidene fluoride (PVDF) and conductive agent acetylene black are mixed in a mass ratio of 92:4:4, and solvent NMP is added and stirred to form a mixed and stable positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and after drying and rolling, a positive electrode sheet is obtained. The positive electrode sheet is a round sheet with a diameter of 1.2 cm.
[0183] (2) Preparation of negative electrode sheet: The negative electrode sheet adopts commercially available metal lithium sheet.
[0184] (3) Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the solute LiPF was added to the organic solvent. 6 Dissolve and mix evenly to obtain an electrolyte; wherein LiPF 6 The concentration is 1.0 mol / L.
[0185] (4) Selection of isolation membrane: Polyethylene film is used as the isolation membrane.
[0186] (5) Battery assembly: Place the items required for the experiment in a 60°C oven for 12 hours for drying.
[0187] The battery assembly sequence is negative electrode shell - metallic lithium (negative electrode sheet) - isolation membrane - positive electrode sheet - gasket - spring - positive electrode shell; the electrolyte is injected into the dry battery cell, and after soaking for 24 hours, it is formed (the voltage is set to 2.5~4.3V), and the battery cell is completed after aging at room temperature for 12 hours.
[0188] 2. Conduct electrochemical performance tests on the assembled battery, including:
[0189] (1) First charge capacity and first discharge capacity test: Place the battery to be tested in a 25°C oven, let it stand for 15 minutes, discharge at 0.3C until the voltage reaches 2.8V, then continue to charge at 0.3C until the voltage reaches 4.25V, let it stand for 5 minutes, charge at 4.25V constant voltage until the current reaches 0.05C, and record the charge capacity at this time as the first charge capacity. Then let it stand for 15 minutes, and then discharge at 0.33C constant current until the voltage reaches 2.8V, and record the rate discharge capacity + constant current discharge capacity = first discharge capacity.
[0190] (2) First efficiency (first coulombic efficiency): First coulombic efficiency = first charge capacity / first discharge capacity*100%.
[0191] (3) Cycle capacity retention rate test: The test batteries of each embodiment and comparative example are installed on a blue-electric test instrument and placed in a (25±1)°C test environment. The following procedures are set: let stand for 10 minutes; charge to 4.3V at a constant current of 0.3C, then charge at a constant voltage until the current drops to 0.05C, and stop charging; let stand for 5 minutes; then discharge to 2.8V at a constant current of 0.3C, and let stand for 10 minutes; record the discharge capacity of the first cycle as the initial capacity; the above is one process, and the above process is repeated subsequently; record the capacity retention rate after 100 cycles, then the capacity retention rate of the 100th cycle = the discharge capacity of the 100th cycle / the discharge capacity of the first cycle.
[0192] The above test results are shown in Table 1.
[0193] (4) Charge and discharge curve test of some embodiments and comparative examples: The test battery (battery of embodiment 3 and comparative example 1) was installed on a blue electric test instrument, placed in a (25±1)℃ test environment, and set the following program: stand for 10 minutes; charge to 4.25V at 0.3C constant current, then charge at constant voltage until the current drops to 0.05C, and then stop charging; stand for 5 minutes; then discharge to 2.8V at 0.3C constant current. The test results are as follows: Figure 1 shown.
[0194] (5) Long cycle curve test of some embodiments and comparative examples: The test batteries (batteries of embodiments 1-5 and comparative example 1) were placed in an environment of 25°C, charged to 4.25V using a current of 1C, then charged to 0.05C at a constant voltage, and left to stand for 30 minutes, and then discharged to 2.8V using a current of 1C, and left to stand for 30 minutes. The above charge and discharge process was repeated until the capacity of the battery was less than 80% of the initial capacity or the test was stopped after 1500 cycles. The test results are as follows: Figure 2 shown.
[0195] The performance test results of the batteries of various embodiments and comparisons are shown in Table 1 below.
[0196] Table 1
[0197]
[0198] It can be seen from the data in Table 1 that compared with Comparative Examples 1-2, the button-type half-cells prepared using the cobalt-free positive electrode materials provided in Examples 1-7 have higher initial charge and discharge capacity, higher first inventory efficiency, and good cycle performance. This shows that the structural stability of the cobalt-free positive electrode materials prepared in the embodiments of the present invention is significantly increased compared with the common or existing materials on the market. Thus, by utilizing the excellent structural stability of the cobalt-free positive electrode material, phase changes can be effectively suppressed, secondary particle cracking can be prevented, and electrolyte corrosion can be reduced, thereby helping to improve the electrochemical properties of the material, such as cycle stability.
[0199] In addition, from Figure 1 and Figure 2 It can also be seen that the charge and discharge curve of Example 3 of the present invention is better than that of Comparative Example 1, and the long cycle curves of Examples 1-5 of the present invention are better than those of Comparative Example 1, indicating that the electrochemical performance of the battery provided by the embodiment of the present invention is better than that of the battery provided by Comparative Example 1.
[0200] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0201] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0202] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0203] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0204] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cobalt-free positive electrode material, characterized in that: The chemical formula of the cobalt-free positive electrode material is Li a Ni x Mg y Al z O2·nB; Among them, 0.9≤a≤1.1, 0<n≤0.1, 0<x<1, 0<y<1, 0<z<1, 1≤x+y+z≤1.2; The cobalt-free positive electrode material has a core-shell structure, and the chemical formula of the core of the cobalt-free positive electrode material is Li a Ni x Mg y Al z O2, wherein Mg is an element doped to replace Li at the alkali metal site, and Al is an element doped to replace Ni at the transition metal site; A coating layer is formed on the surface of the core, and the coating layer contains element B.
2. The cobalt-free positive electrode material according to claim 1, characterized in that The x, y, and z satisfy: 0.6≤x≤0.95, 0<y≤0.2, 0<z≤0.2; And / or, a satisfies: 0.95≤a≤1.05; And / or, x, y and z satisfy: 1.05≤x+y+z≤1.
1.
3. The cobalt-free positive electrode material according to claim 1, characterized in that The particle size Dv50 of the core is 1 μm to 8 μm; And / or, the coating layer has a thickness of 2 nm to 10 nm.
4. The cobalt-free positive electrode material according to any one of claims 1 to 3, characterized in that: The element B exists in at least one of the following forms: (1) forming a coating layer on the surface of the core; (2) replace nickel ions in the lithium nickelate lattice; (3) Replace lithium ions in the lithium nickel oxide lattice.
5. The method for preparing a cobalt-free positive electrode material according to any one of claims 1 to 4, characterized in that: The method comprises: Mixing the nickel-containing compound, the co-solvent and water to obtain a mixed solution; Adding a magnesium-containing compound and an aluminum-containing compound to the mixed solution, and obtaining a precursor after mixing, separating and drying; The precursor is mixed with a boron-containing compound and a lithium-containing compound, and sintered to obtain the cobalt-free positive electrode material.
6. The method for preparing a cobalt-free positive electrode material according to claim 5, characterized in that: The nickel-containing compound includes at least one of nickel hydroxide, nickel chloride or nickel nitrite; and / or, the cosolvent comprises polyvinyl pyrrolidone; and / or, the magnesium-containing compound comprises at least one of magnesium chloride, magnesium hydroxide, magnesium nitrate or magnesium sulfite; and / or, the aluminum-containing compound comprises at least one of sodium aluminate, aluminum hydroxide, aluminum carbonate or aluminum sulfite; and / or, the boron-containing compound comprises at least one of boric acid, boron chloride or boron oxide; And / or, the lithium-containing compound includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate or lithium chloride.
7. The method for preparing a cobalt-free positive electrode material according to claim 5, characterized in that: The mass ratio of the nickel-containing compound to the co-solvent is (10-25):1; And / or, the nickel-containing compound, the co-solvent and water are mixed, and then stirred at a temperature of 60° C. to 80° C. for 1 h to 4 h to obtain a mixed solution; and / or, the particle size Dv50 of the precursor is 3 μm to 5 μm; And / or, the tap density of the precursor is 1.5 to 1.9 g / cm 3 .
8. The method for preparing a cobalt-free positive electrode material according to any one of claims 5 to 7, characterized in that: In the step of obtaining the precursor, a magnesium-containing compound is first added to the mixed solution and stirred for 1 h to 5 h, and then an aluminum-containing compound is added to the mixed solution and stirred for 2 h to 5 h. After mixing evenly, separation, washing and drying are performed; And / or, in the step of obtaining the cobalt-free positive electrode material, the precursor, the boron-containing compound and the lithium-containing compound are mixed according to the molar ratio of Ni:Mg:Al:B:Li=x:y:z:n:a, and then preheated at 300°C to 500°C for 4h to 8h, and then sintered at 600°C to 820°C for 10h to 16h to obtain the cobalt-free positive electrode material.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the cobalt-free positive electrode material according to any one of claims 1 to 4, or the cobalt-free positive electrode material prepared by the method according to any one of claims 5 to 8.
10. A battery, characterized in that: The battery comprises the cobalt-free positive electrode material according to any one of claims 1 to 4, or the cobalt-free positive electrode material prepared by the method according to any one of claims 5 to 8, or the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Method for preparing modified spinelle manganic acid lithium material and lithium secondary battery
CN101038965A
Preparation method of iron-containing lithium-enriched manganese-based positive electrode material
CN104300141A
Preparation method of lithium-ion positive electrode material
CN104300143A
High-nickel ternary positive electrode material as well as preparation method and application thereof
CN112614991A
Cobalt-free positive electrode material and precursor and preparation method thereof
CN115057489A